Video edukasi cara mencuci hidung yang benar sebagai salah satu upaya pencegahan Covid-19 - Eka Arie Yuliyani; Rika Hastuti Setyorini; Eva Triani; Indana Eva Ajmala; Nurul Imaniaty As-syarifiah; Mochamad Fauzi Aulia Akbar (Universitas Mataram, 2021)
The nasal epithelium and nasopharyngeal mucosa are the main entry points and sites of SARS-CoV-2 replication. Therefore, it is very important to be able to maintain the health of the nasal and oral cavities during this pandemic, namely by nasal washing with salt water and gargling. Nasal washing is a practical, simple, economical, and feasible method to be applied in everyday as well as a non-pharmacological therapy to clean the nasal cavity from various microorganisms including reducing the number of viruses in the nasal cavity, so education about this is considered important to do. Online education is the right choice during this pandemic because people do more work from home and information about various things, including information about health, can be accessed quickly. This is an opportunity for health workers to provide education to the community, one of which is through a nasal washing video where in this video we discuss knowledge about nasal washing, its benefits and especially how to do it properly. In addition, the public can also provide input about this educational video through the google form, so that it can be suggestions for improvements in the future